ANALISIS IMPLEMENTASI LAYANAN PENDIDIKAN UNTUK ANAK DENGAN DOWN SYNDROME DI SLB NEGERI KELEYAN - Utfa, Lailatul; Estu Harsiwi, Nova (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to analyze educational services for children with Down Syndrome at SLB Negeri Keleyan. The research employed a qualitative approach with a case study method, using in-depth interviews, direct observation, and documentation. The findings reveal that educational services at SLB Negeri Keleyan involve adaptive and individualized teaching strategies, emphasis on daily living skills, the role of teachers as both emotional and academic facilitators, and strong collaboration with parents. Challenges identified include the limited number of special education teachers, insufficient inclusive learning facilities, and the lack of flexible curriculum design. These results suggest that the success of educational services for children with Down Syndrome depends not only on pedagogical approaches but also on synergy among teachers, families, and school environments. The study recommends strengthening teacher competencies, providing adaptive learning tools, and encouraging active parental involvement in the educational process.